Load sequence effects and cyclic deformation behaviour of 7075-T651 aluminium alloy. (February 2022) - Branco, R.; Costa, J.D.; Prates, P.A.; Berto, F.; Pereira, C.; Mateus, A.
Highlights: Strain-controlled fatigue behavior of 7075-T651 under step loading is studied; Cyclic behaviour is simulated using a nonlinear isotropic-kinematic hardening law; Fatigue life is predicted by using strain-based, energy-based, and SWT-based parameters; Predictions based on the SWT parameter provide close correlations with the experiments. Abstract: This paper investigates the effect of loading history on cyclic deformation and fatigue behaviour of 7075-T651 aluminium alloy subjected to two-step loading. High-low and low–high sequences, encompassing both symmetrical and asymmetrical steps, are performed under strain control for different loading scenarios. An elastic–plastic constitutive model is developed using the finite element method to simulate the stabilised stress–strain response. Fatigue life predictions are made by applying strain-based, energy-based, and SWT-based methods. The SWT-based model properly captured the effect of load history on fatigue behaviour. In addition, fatigue life predictions carried out using the numerical simulations were in agreement with the experimental results.